PENGARUH PEMBELAJARAN KOOPERATIF MODEL INVESTIGASI KELOMPOK TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (Tanjungpura University, 2018)
The success of the learning process can’t be separated from the ability of teachers to apply learning models. Learning models that are often applied by classroom teachers are conventional learning models that tend to minimize student involvement. The purpose of this research is to know the influence of cooperative learning model of group investigation on student learning outcomes in the subjects of civic education in class X SMK Negeri 1 Muara Pawan Ketapang. The method used in this research is an experimental method of quantitative approach. The research design in this research is the true experimental design method, which is the pretest posttest control group design model. The population is 30 students and 1 teacher. Results of experimental class study X ATP (Plantation Crop Agribusiness) average value = 80.84. Control class X ATPH average value of learning outcomes under KKM (Criterion Minimum Completion) 75 that is = 73,34. The conclusion is the result of student learning using cooperative learning model of group investigation better than student learning result using conventional learning model.